MANAJEMEN KURIKULUM PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PEMBIASAAN SHALAT DHUHA - Mursal Aziz; Muhammad Walimsyah Sitorus; Asriyani Asriyani (MPI STAI Sangatta Kutai Timur, 2025)
This study aims to analyze the management of the Islamic Education curriculum in shaping students' religious character. It focuses on the habit of praying the Dhuha prayer at MIS Al-Washliyah Langgeng Sari. The study employs a qualitative approach, using a case study design. Research subjects included the principal, Islamic Education teachers, students, and parents. Data collection was conducted through observation, interviews, and documentation. Data analysis used a data condensation model, data presentation, and conclusion drawing. The results show that the management curriculum has been implemented systematically in three main stages: planning, implementation, and evaluation. Planning integrates religious values in all school activities. The habit of praying Dhuha is implemented routinely and in a structured manner. It is supported by teacher role models and a fun learning approach. Evaluation is carried out authentically by observing changes in student behavior. The habit of praying Dhuha has proven to positively impact students' religious character. These include discipline, responsibility, honesty, and empathy. However, there are still obstacles, such as a lack of student awareness and parental support. Therefore, synergy is needed between schools and families to optimize the formation of students' religious character sustainably.